Peningkatan Minat Siswa pada Teknologi Informasi melalui Edukasi Jaringan LAN di SMP Negeri 6 Kota Sorong (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid development of information technology requires improved digital literacy and basic technological skills beginning at the secondary education level. One important competency that needs to be introduced to students is an understanding of computer networks, particularly Local Area Networks (LAN), along with the development of communication and public speaking skills as essential soft skills. This activity aimed to increase the interest and understanding of students at SMP Negeri 6 Sorong City regarding information technology through LAN network education integrated with public speaking training. The activity was implemented using an experiential learning approach combined with student-centered learning, which emphasized active student participation through material presentations, demonstrations, hands-on network cabling practice, and interactive discussions. The program was conducted in three main stages: preparation, implementation, and closing evaluation. The results indicated that students were able to follow all learning activities effectively and demonstrated strong enthusiasm in understanding basic LAN network concepts and cabling techniques. Additionally, students showed increased confidence in expressing ideas and actively participating in discussions. The integration of technical training and soft skill development created a more contextual, engaging, and practical learning environment. This activity also provided valuable experience for the community service team in strengthening communication abilities and applying academic knowledge in real educational settings. Overall, the practice-based LAN education program proved to be an effective approach for increasing students’ interest in information technology while simultaneously developing communication skills from an early age.